Risk factors for vascular dementia in elderly psychiatric outpatients with preserved cognitive functions - Stella, Florindo [UNESP]; Banzato, Claudio E.M. [UNESP]; Gasparetto Sé, Elisandra Villela [UNESP]; Scudeler, Juliana Leme [UNESP]; Pacheco, Jaime Lisandro [UNESP]; Kajita, Romeu Toshiyuki [UNESP] (Elsevier, 2007)
The aim of the study was to assess risk factors for vascular dementia (VaD) in elderly psychiatric outpatients without dementia, and to determine to what extent clinical interventions targeted such risk factors. Out of 250 clinical charts, 78 were selected of patients over 60 years old, who showed no signs of dementia. Information was obtained regarding demographics, clinical conditions (diagnosis according to ICD-10), complementary investigation, cognitive functions (via CAMCOG), neuroimaging, and the presence of risk factors for VaD. Depression was the most prevalent psychiatric disorder (74%). A great majority of the patients (86%) had at least one risk factor for VaD. One-third of the sample showed three or more risk factors for VaD. The clinical conditions related to risk factors for VaD were hypertension (48.7%), heart disease (30.8%), hypercholesterolemia (25.6%), diabetes mellitus (23.1%), stroke (12.8%), tryglyceride (12.8%), and obesity (5.1%). In terms of lifestyle, smoking (19.2%), alcohol abuse (16.7%), and sedentarism (14.1%) were other risk factors found. Definite risk factors for VaD were found in 83.3% of the patients. Previous interventions targeting risk factors were found in only 20% of the cases. The high rates of risk factors for VaD identified in this sample suggest that psychiatrists should be more attentive to these factors for the prevention of VaD. © 2007 Elsevier B.V. All rights reserved.
Keywords: Elderly psychiatric outpatients; Risk factors; Vascular dementia; triacylglycerol; adult; aged; alcohol abuse; cognition; depression; diabetes mellitus; disease classification; elderly care; female; heart disease; human; hypercholesterolemia; hypertension; major clinical study; male; mental disease; multiinfarct dementia; neuroimaging; obesity; outpatient; priority journal; risk factor; sitting; smoking; stroke; Aged; Aged, 80 and over; Alcoholism; Cardiovascular Diseases; Cerebrovascular Accident; Comorbidity; Dementia, Vascular; Depressive Disorder; Diabetes Complications; Female; Heart Diseases; Humans; Hyperlipidemias; Hypertension; Male; Mental Disorders; Middle Aged; Obesity; Physical Fitness; Retrospective Studies; Risk Factors; Smoking